Buffering roles of (pro)renin receptor in starvation‐induced autophagy of skeletal muscles. Issue 5 (27th February 2018) - Mizuguchi, Yuki; Yatabe, Midori; Morishima, Noriko; Morimoto, Satoshi; Ichihara, Atsuhiro
Abstract: Autophagy is an intracellular catabolic process contributing to the regulation of nutrient homeostasis and cellular remodeling. Studies revealed that the nuclear translocation of transcription factor EB (TFEB) plays a key role in lysosomal biogenesis and autophagic pathways. The (pro)renin receptor [(P)RR] is a multifunctional protein playing a pivotal role in regulation of the tissue renin–angiotensin system and is known as an essential constituent of vacuolar H + ‐ATPase, considered to be necessary for the autophagy–lysosome pathway. On the basis of these findings, we postulated that (P)RR may also contribute to the regulation of starvation‐induced autophagy. In this study, starvation increased the expression of (P)RR and autophagy‐related genes, especially, in the skeletal muscles of mice. In C2C12 mouse myoblast cells, starvation increased (P)RR expression and TFEB translocation, leading to the expression of autophagy‐related genes. Knockdown of (P)RR enhanced both the TFEB translocation to the nucleus and the expression of autophagy‐related genes during starvation. These results suggest that (P)RR plays a buffering role in starvation‐induced autophagy by affecting the nuclear translocation of TFEB. Thus, (P)RR, which increases during starvation, is one of the important factors that control autophagy in the skeletal muscles. (P)RR may act as a buffer to reduce excessive TFEB‐dependent autophagy flux. Abstract : The (pro)renin receptor [(P)RR], an important constituent of vacuolar H + ‐ATPase, was increased in the skeletal muscles during starvation. While starvation promoted the nuclear translocation of transcription factor EB (TFEB) and the expression of autophagy‐related genes, knockdown of (P)RR enhanced both the TFEB translocation to the nucleus and the expression of autophagy‐related genes during starvation. These results suggest that (P)RR plays a buffering role in starvation‐induced autophagy by reducing excessive TFEB‐dependent autophagy flux.